The Effect of Problem-Based Learning in Reducing the Misconceptions of Junior High School Learners on the Material of Substance Pressure - Bajongga Silaban; Parlindungan Sitorus; Leni Marlina Lase (Jurnal Amal Pendidikan, 2023)
Various things experienced by science teachers (physics) in delivering material to students, especially the difficulty of absorbing and understanding the concepts conveyed by the teacher. This can be caused by the teacher's lack of understanding of the characteristics of the students themselves, and also the lack of concentration in following the learning material presented by the teacher starting from the introduction, core activities and closing so that the knowledge gained is only a piece of it. This study aims to determine the effect of problem-based learning on reducing students' misconceptions through students' learning outcomes on pressure material at state junior high school 7 Medan. This research is a pre-experimental design of one-group pretest-posttest type. The sampling technique used was purposive sampling considering that 8th-1 class is heterogeneous, consisting of different genders, religions, ethnicities, and races. The results showed that the indicator knew the concept 42%, did not understand 17.67%, and misconceptions 40.33%. After being given the problem-based learning action, knowing the concept increased by 34%, not understanding and misconceptions decreased to 8% and 25.66% respectively. Furthermore, t-test was conducted to determine the difference before and after treatment, obtained t-count = 26 with t-table = 2.04 at a significance level of 0.05, so Ha was accepted. The average value of <N-Gain> of 0.6 is classified as moderate which indicates that 60% of problem-based learning variables can improve concept understanding and reduce misconceptions on the material of substance pressure of state junior high school 7 Medan students.